The Sociolinguistics of Translating Canonical Religious Texts - Nida, Eugene (TTR, 1994)
AbstractThe sociolinguistics of Translating Canonical Religious Texts — Discussions of the theory and practice of translating have largely neglected the sociolinguistic factors in translating. This is particularly true in the case of religious texts, in which problems of textual variants, historical criticism, the power of tradition, the tensions between form and content, orality, format, diversities of genres, and interpretive notes play such an important role. As a result, multiple translations of such texts are generally required because of the diverse backgrounds of readers and the various uses of religious texts, for example, study, devotion, proclamation, and liturgy.